Effect of ibuprofen on the swimming pattern of cyprinus carpio - Eissa, Bettina Lorena (2014)
Ibuprofen is a non-selective inhibitor of cyclooxygenasewith antiinflammatory, antipyretic and analgesicactivity; its mechanism of action involves the inhibition ofprostaglandins biosynthesis. Its presence in water-bodies ofperi-urban areas as a result of domestic discharges is highlyfrequent. The aim of this paper was to evaluate the impactof drug exposure on some parameters of the swimmingbehaviour of the common carp under laboratory conditions.Semi-static bioassays were carried out with juveniles ofCyprinus carpio as test organisms. Assays comprised threeperiods: acclimation (7 days in tap water [TW]), control(4 days in TW) and exposure (13 days in TW + 100 μg.L-1ibuprofen). During control and exposure, the parameterswere registered to calculate swimming activity (as RelativeActivity Index; Ia) and swimming velocity. The druginhibited the swimming activity with symptoms correspondingto Hypo-Hyperactivity Syndrome of Drummondand Russom; swimming velocity was slightly reduced.There were no lethal effects registered in any case. It wasthen concluded that, under assay conditions, Ia representsa suitable behavioural biomarker for assessing ibuprofeneffects on swimming activity of Cyprinus carpio.